First-Line Treatments for Metastatic Clear Cell Renal Cell Carcinoma: An Ever-Enlarging Landscape. (1st February 2022) - Gulati, Shuchi; Labaki, Chris; Karachaliou, Georgia Sofia; Choueiri, Toni K; Zhang, Tian
Abstract: Treatment paradigm for metastatic clear cell renal cell carcinoma (mccRCC) has changed dramatically over the recent decades. From cytokines, interleukin-2 and interferon-α to tyrosine kinase inhibitors and mammalian target of rapamycin inhibitors, during the last decade, combinations of immune checkpoint inhibitors have taken over first-line treatment of mccRCC. These combinations are approved based on results from large phase III clinical trials, all of which used sunitinib as the comparator. These trials include CheckMate214 (ipilimumab plus nivolumab), KEYNOTE 426 (pembrolizumab plus axitinib), JAVELIN Renal 101 (avelumab plus axitinib), CheckMate 9ER (nivolumab plus cabozantinib), and the CLEAR study (lenvatinib and pembrolizumab). Results from these studies constitute milestones for newer therapeutic approaches in mccRCC. The broadening spectrum of treatment options for patients with mccRCC with multiple first-line options currently available also means that treating physicians will need to consider each option carefully, balance clinical factors, financial considerations, and weigh toxicity profiles of each drug before deciding the optimal treatment regimen for each individual patient. We describe each frontline treatment option in detail through this review to aid the decision-making process. Abstract : Management of metastatic clear cell renal cell carcinoma (mccRCC) has progressed to the point that immune checkpoint inhibitor (ICI) combinations or ICI/TKI combinations have become standard of care. This article highlights the current therapeutic landscape for patients with mccRCC in the first-line setting and explores the specific considerations relative to currently approved regimens, along with future perspectives.